Combination of Interventions Needed to Improve Maternal Healthcare Utilization: A Multinomial Analysis of the Inequity in Place of Childbirth in Afghanistan - Kim, Christine; Erim, Daniel; Natiq, Kayhan; Salehi, Ahmad Shah; Zeng, Wu (Frontiers in Global Women's Health, 2020)
Giving birth with a skilled birth attendant at a facility that provides emergency obstetric care services has better outcomes, but many women do not have access to these services in low- and middle-income countries. Individual, household, and societal factors influence women’s decisions about place of birth. Factors influencing birthplace preference by type of provider and level of public facility are not well understood. Applying the Anderson Behavioral Model of healthcare services use, we explored the association between characteristics of women and their choice of childbirth location using a multinomial logistic regression, and conducted a scenario analysis to predict changes in the childbirth location by imposing various interventions. Most women gave birth at home (68.1%), while 15.1% gave birth at a public clinic, 12.1% at a public hospital, and 4.7% at a private facility. Women with higher levels of education, from households in the upper two wealth quintiles, and who had any antenatal care were more likely to give birth in public or private facilities than at home. A combination of multisector interventions had the strongest signals from the model for increasing the predicted probability of in-facility childbirths. This study enhances our understanding of factors associated with the use of public facilities and the private sector for childbirth in Afghanistan. Policymakers and healthcare providers should seek to improve equity in the delivery of health services. This study highlights the need for decisionmakers to consider a combination of multisector efforts, (e.g., health, education, and social protection) to increase equitable use of maternal healthcare services.